1998
DOI: 10.1002/(sici)1099-1085(19980630)12:8<1357::aid-hyp619>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological modelling of rivers with erodible banks

Abstract: Abstract:A bank erosion mechanism and provisions to account for the associated planform changes and input of bank erosion products are added to a two-dimensional, depth-averaged model of river morphology. The model is applied to a reach of the meandering gravel-bed River OhrÏ e (Eger) in the former state of Czechoslovakia. The agreement with observations is poor, but this can be ascribed to shortcomings in the¯ow and bed topography submodels rather than to shortcomings in the bank erosion submodel. Better resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…The PEEP-3 system and the TCT principle offer considerable potential here to test and improve not only geotechnical stability models which attempt to embrace such effects, but also a full range of bank erosion models, assumptions and predictions (e.g. Hasegawa, 1989;Darby, 2000;Mosselman, 2000). This is vital to a sound process understanding of the mechanics of bank instability, the fate of failed material, operation of basal clean-out cycles (Thorne, 1982) and the delivery and storage of bank sediment to river systems, especially time-lags between hydrograph peaks, erosion events, and sediment injection to rivers and estuaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEEP-3 system and the TCT principle offer considerable potential here to test and improve not only geotechnical stability models which attempt to embrace such effects, but also a full range of bank erosion models, assumptions and predictions (e.g. Hasegawa, 1989;Darby, 2000;Mosselman, 2000). This is vital to a sound process understanding of the mechanics of bank instability, the fate of failed material, operation of basal clean-out cycles (Thorne, 1982) and the delivery and storage of bank sediment to river systems, especially time-lags between hydrograph peaks, erosion events, and sediment injection to rivers and estuaries.…”
Section: Discussionmentioning
confidence: 99%
“…This hinders process specification, because of difficulties in 'matching up' and then quantifying a given response to a specific, imposed stress, which is often a useful route to quantitative exploration of dominant processes and theory testing. For instance, despite the explosion of bank erosion research over the last 15 years, Mosselman (2000) still found that inadequate process specification was one of the many reasons for poor model predictions of bank erosion rates. The hypotheses below illustrate some of these difficulties.…”
Section: The 'Resolution Mismatch' Implicationmentioning
confidence: 99%
“…Another, more recent modeling strategy involves two-and three-dimensional computational fluid dynamics [e.g., Shimizu et al, 1990;Ferguson et al, 2003;Duan and Julien, 2005;Ruther and Olsen, 2007]. These numerical flow simulations have been coupled with models of bed material transport [e.g., Li et al, 2008;Vasquez et al, 2008] and bank erosion [e.g., Mosselman, 1998;Darby et al, 2002;Rinaldi et al, 2008] as a means of predicting the evolution of channel form [e.g., Fischer-Antze et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Deterministic models are usually physically based and use the equations of river morphodynamics (Seminara, 1998; coupled to some empirical model equations of vegetation development. Such models are particularly well developed for meandering rivers (Tubino and Seminara, 1990;Mosselman, 1998;Imran et al, 1999;Zolezzi and Seminara, 2001;, the dynamics of which has been widely investigated via both extensive numerical simulations, and analytical techniques. Promising results have however recently been obtained with regard to the branching dynamics that characterize braided rivers (Murray and Paola, 2003;Bolla Pittaluga et al, 2003;Coulthard et al, 2007;Jang and Shimizu, 2007;Bertoldi et al, 2006;Bertoldi and Tubino, 2007).…”
Section: Introductionmentioning
confidence: 99%